INTERNATIONAL RELATIONS AND DIPLOMATIC SERVICE: RETROSPECTIVE ANALYSIS AND PROSPECTS OF THE NEW WORLD ORDER - E. V. Ohotskii (Vestnik MGIMO-Universiteta)
This article presented as a review to the textbook of the Doctor of History Shakhalilov Shamansur, The History of International Relations: Driving Forces, Global Tendencies. Moscow State University Press, 2015. The author focuses readers attention on the regularities of formation, development and peculiarities of legal regulation of international relations, considers these relations as an ongoing, highly controversial and multidirectional developing process of the formation of the world system of States and international relations, explores the driving forces, events and phenomena, who had in his time, and many still have a decisive influence on international policy the leading powers of the world in the framework of nonlinear processes of globalization and the current, seriously flawed by today's standards, world order and system of international law. The article draws readers attention to everything presented in the tutorial main substantial characteristics and patterns of international relations in their historical context. Emphasizes the inadmissibility of violations of principles and norms of functioning of the traditional system of international law; analyses the factors of influence on the world trends of globalization processes is the gradual destruction of the boundaries between national and international levels of government and governance, the increasing role of supranational political actors. Attention is drawn to the increasing importance in international Affairs information and communication technologies and social networks, expanding the access of citizens to discuss government decisions on international issues. Article will help not only students, but all interested in the patterns, principles and features of international practices in different historical periods and in different civilization. Will foster in the reader a holistic view of the system of international relations and diplomatic activities, to learn, to understand the origins, motivations and basic principles of foreign policy in different historical and structural conditions, a deeper understanding of the relevant definitions, concepts, norms and traditions of international relations and the professional culture in diplomacy.